Rationale and Design of the First Double-Blind, Placebo-Controlled Trial with Allogeneic Adipose Tissue-Derived Stromal Cell Therapy in Patients with Ischemic Heart Failure: A Phase II Danish Multicentre Study - Jens Kastrup; Morten Schou; Ida Gustafsson; Olav W. Nielsen; Rasmus Møgelvang; Klaus F. Kofoed; Charlotte Kragelund; Jens Dahlgaard Hove; Andreas Fabricius-Bjerre; Merete Heitman; Mandana Haack-Sørensen; Lisbeth Drozd Lund; et al. (Hindawi Limited, 2017)
Background. Ischemic heart failure (IHF) has a poor prognosis in spite of optimal therapy. We have established a new allogeneic Cardiology Stem Cell Centre adipose-derived stromal cell (CSCC_ASC) product from healthy donors. It is produced without animal products, in closed bioreactor systems and cryopreserved as an off-the-shelf product ready to use. Study Design. A multicentre, double-blind, placebo-controlled phase II study with direct intramyocardial injections of allogeneic CSCC_ASC in patients with chronic IHF. A total of 81 patients will be randomised at 2 : 1 to CSCC_ASC or placebo. There is no HLA tissue type matching needed between the patients and the donors. Methods. The treatment will be delivered by direct injections into the myocardium. The primary endpoint is change in the left ventricle endsystolic volume at 6-month follow-up. Secondary endpoints are safety and changes in left ventricle ejection fraction, myocardial mass, stroke volume, and cardiac output. Other secondary endpoints are change in clinical symptoms, 6-minute walking test, and the quality of life after 6 and 12 months. Conclusion. The aim of the present study is to demonstrate safety and the regenerative efficacy of the allogeneic CSCC_ASC product from healthy donors in a double-blind, placebo-controlled, multicentre study in patients with IHF.